Chinese-German computational and applied mathematics - Hoppe, Ronald H. W.; Hu, Jun; Peter, Malte A.; Rannacher, Rolf; Shi, Zhongci; Xu, Xuejun (Computational methods in applied mathematics, 2016)
Abstract This short article is the epilog of the 14 preceding papers in this and the previous issue of CMAM. All are extracted from the 5th Chinese-German Workshop on Computational and Applied Mathematics - at Augsburg but submitted as individual papers to the journal.
Gesehen am 20.05.2020